Work-Life Balance as Mediator Between Workplace Spirituality, Organizational Commitment, and Job Satisfaction - Joshi, Akashdeep; Kumar, Dinesh; ., Shabnam (Prabandhan: Indian Journal of Management, 2024)
Purpose : The present study investigated the mediating role of work-life balance on the relationship between workplace spirituality, organizational commitment, and job satisfaction among banking sector employees in Northern India. Methodology : The study followed a descriptive cross-sectional research design using a survey approach in the form of a questionnaire. Data were collected from 218 employees in both public and private sector banks in northern India and were analyzed using structural equation modeling (SEM). Findings : The study’s findings suggested that the perception of work-life balance fully mediated the relationship between meaningfulness in work and its outcomes. However, when it comes to alignment with organizational values, work-life balance serves as a partial mediator in the relationship. Practical Implications : The study provided important implications for management practitioners to adopt work-life balance policies in order to fully realize the benefits of workplace spirituality. Originality : The study has filled an important research gap in the mediation effect of work-life balance vis-à-vis the impact of workplace spirituality on organizational commitment and job satisfaction, especially in the Indian context.